“We Need to Build Carbon-Neutral Houses” – Discourses of Responsible Expertise in Finnish Professional Media - Kääntä, Liisa; Koskela, Merja; Syrjälä, Henna; Salmela, Eveliina (Taylor & Francis, 2024)
In this study, we explore how expertise and responsibility are discursively intertwined in professional media. Based on quotations from building and real-estate industry professionals in news texts concerning sustainable building and housing, we identified three responsibility-related discourses: responsibility as a strategic professional vision, responsibility as techno-material expertise, and responsibility as a communal and societal orientation. These discourses of responsible expertise are important for voicing professional perspectives and emphasizing corporate social responsibility (CSR). In the sustainability transition, industry professionals are balancing between organizational and industry-level motives, between utility perspectives for “us” and “others,” and between managing impressions of doing good for the industry and for citizens or society at large. Through and with journalism, these professionals disseminate both individual and organizational expertise to the public in order to “make the industry and the whole society better and more sustainable.”
Keywords: Building and real-estate industry; discursive construction of expertise; professional media; responsibility; sustainable building; fi=Markkinointi|en=Marketing|; fi=Viestintätieteet|en=Communication Studies|